KESALAHAN BERBAHASA PRODUKTIF GURU-GURU TK DI KECAMATAN SAMBENG - Darwati Darwati (EDU-KATA, 2018)
The objectives of this research are : (1) to know the kindergarten teachers’ competence in writing, and (2) to know the kindergarten teachers’ productive language errors.The data collection is done by using writing and speaking techniques. The data analysis is done using interactive model suggested by Miles and Huberman, that consists of : (1) data reduction, (2) data display and (3) conclusion drawing.The results of the research show that there is a lot of problem in teeachers’ language competence. In writing there are some errors made by the teachers. The errors consists of (1) the errors in using punctuation, (2) the writing of prefixes, (3) the wrong writing of preposition, (4) the double use of copula, (5) the wrong writing of words, (6) false reasoning’s, (7) the wrong writing of conjunction, and (8) interference.